Katherine Mansfield’s Many Windows - Kascakova, Janka (Hungarian Journal of English and American Studies, 2022)
Book review:Davison, Claire and Gerri Kimber, eds. The Edinburgh Edition of the Collected Letters of Katherine Mansfield, Volume 1. Letters to Correspondents A-J. Edinburgh: Edinburgh UP, 2020. 680 pages. ISBN 9781474445443. Hb. £175.